Lymphoma and Leukemia of the Nervous System - Batchelor, Tracy; DeAngelis, Lisa M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Lymphomas and leukemias of the nervous system result in devastating neurological complications and high mortality. These malignancies may arise within the central nervous system or may disseminate to the brain or cerebrospinal fluid from a source elsewhere in the body. Early diagnosis and therapeutic intervention lead to improvement in neurological symptoms and signs and potentially improved survival. The diagnostic evaluation and treatment of lymphoma and leukemia of the nervous system differ from the standard approaches used when the disease is confined outside of the nervous system. Lymphoma and Leukemia of the Nervous System is a comprehensive review of this challenging group of diseases and should be useful for the practicing neurologist, hematologist, oncologist and for any practitioner involved in the management of these patients.   Review of the first edition   This book, the first devoted primarily to the disease (Primary CNS Lymphoma), provides a comprehensive source for the study of the clinical features, diagnostic aspects, and approaches of lymphoma treatment. Although the main focus of the book is primary central nervous system lymphoma, several contributing authors also provide high-quality chapters on the neurologic manifestations of non-Hodgkin's lymphoma, Hodgkin's disease, and plasma-cell disorders and the neurologic complications of lymphoma therapy. This book — up-to-date, concise, and clearly written — provides a review of the disease that is more in-depth than that found even in subspecialty textbooks.   Joachim Yahalom, M.D., Department of Radiation Oncology Memorial Sloan-Kettering Cancer Center New England Journal of Medicine.
Foreword -- Preface -- Part I – Introduction -- Chapter 1- Overview of the Lymphomas – Jill Lacy, Julie Vose -- Chapter 2- Overview of the Leukemias – Harshabad Singh, Eyal Attar -- Part II –Central Nervous System Lymphomas -- Chapter 3- Pathological features of CNS lymphomas – Judith Ferry, Rolf Pfannl, Nancy Harris -- Primary CNS lymphoma -- Chapter 4- Epidemiology – Brian O’Neill, Ingfrid Haldorsen -- Chapter 5- Biology – James Rubenstein -- Chapter 6- Diagnostic Considerations – Tracy Batchelor, Daphne Wang, Edward Neuwelt, Gilbert Gonzalez -- Chapter 7- Radiation and Combined Modality Therapy – Lisa DeAngelis, Joachim Yahalom -- Chapter 8- Chemotherapy – Tracy Batchelor, Andrew Grigg, Eckhard Thiel -- Chapter 9- High-dose chemotherapy – Gerald Illerhaus, Carole Soussain, Patrick Johnston -- Variants of CNS lymphoma -- Chapter 10- CNS Lymphoma in the immunocompromised host – Silvia Montoto, Andrew Lister -- Chapter 11- CNS Post-Transplant Lymphoproliferative Disorder – David Schiff, Samar Issa -- Chapter 12- Ocular Lymphoma – Andres Ferreri, Jose Pulido -- Chapter 13- Neurolymphomatosis – Tali Siegal, Joachim Baehring -- Chapter 14- Intravascular Lymphoma of the CNS – Emanuele Zucca, Jon Glass, Maurilio Ponzoni -- Chapter 15- Rare variants of PCNSL (T-cell, low-grade, pediatrics) – Kristoph Jahnke, Oussama Abla, Tamara Shenkier -- Part III - Neurological Complications of Lymphomas and Leukemias -- Chapter 16- Neurological complications of non-Hodgkin lymphoma – Antonio Omuro, Mark Gilbert -- Chapter 17- Neurological complications of Hodgkin lymphoma – Elizabeth Gerstner, Maciej Mrugala -- Chapter 18- Neurological complications of Plasma Cell Disorders – Jan Drappatz, Kurt Jaeckle -- Chapter 19- Neurological complications of acute and chronic leukemias – Marc Chamberlain -- Chapter 20- Paraneoplastic syndromes in hematological malignancies – Josep Dalmau -- Part IV – Neurological Complications of Therapy for Lymphomas and Leukemias -- Chapter 21- Neurological complications of radiation in lymphoma and leukemia patients –Denise Correa, Lisa DeAngelis -- Chapter 22- Neurological complications of chemotherapy in lymphoma and leukemia patients – Patrick Wen -- Chapter 23- Neurological complications of bone marrow transplantation in lymphoma and leukemia patients – Warren Mason, Jacoline Bromberg.
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.